Heterologous prime-boost immunization combining parenteral and mucosal routes with different adjuvants mounts long-lived CD4+ T cell responses in lungs - Kavishna, Ranmali; Olafsdottir, Thorunn Asta; Brynjólfsson, Siggeir F.; Christensen, Dennis; Gustafsson-Hedberg, Tobias; Andersen, Peter; Terrinoni, Manuela; Holmgren, Jan; Harandi, Ali M. (Frontiers in Immunology, 2025)
IntroductionAirway mucosa represents the main entry point for several human pathogens, and as such vaccines against respiratory diseases should ideally elicit protective immune responses in the airways. We have previously reported two immunomodulatory adjuvants based on non-toxic derivatives of Cholera toxin (CT), namely mmCT and CTB-CpG with strong ability to mount mucosal immune responses.MethodsHerein, we aimed to pinpoint the potential of prime-boost immunization approaches using the fusion-protein based Mycobacterium tuberculosis subunit vaccine candidate H56 as a model antigen, combined with adjuvants CAF01, mmCT, and CTB-CpG in mice. This included a parenteral H56+CAF01 priming followed by an intranasal boost with H56+CAF01, H56+mmCT, or H56+CTB-CpG, compared with repeated homologous intranasal administrations of H56 with each adjuvant.ResultsWe observed that a parenteral prime with H56+CAF01 followed by an intranasal H56+CTB-CpG booster immunization triggered a Th1-skewed immune response. Conversely, combining the parenteral H56+CAF01 prime with an intranasal H56+mmCT boost resulted in a mixed Th1/Th17-skewed immune response. Notably, the latter combination also engendered anamnestic, long-lived T-cell responses in the lungs which homologous intranasal H56+mmCT immunizations failed to induce.DiscussionThese results suggest that an immunization regimen consists of parenteral priming with H56+CAF01 followed by an airway boosting with H56 protein and mucosal adjuvants holds promise in mounting combined systemic and mucosal immune responses to Mycobacterium tuberculosis, and as such warrants further exploration. Given the rising interest in mucosal vaccines for respiratory pathogens, these findings offer an important immunological framework for future translational studies.